World Reaction and the Role of Turkiye, Iran and Asian Countries in Maintaining Qatar Sovereignty: A Case Study of Gulf Crisis - Nor Atika Hairi (USIM Press, 2024)
Jurnal Sains Insani Volume 8 No 2 Page (168-173)